2020
DOI: 10.3390/a13040076
|View full text |Cite
|
Sign up to set email alerts
|

Experiments-Based Comparison of Different Power Controllers for a Solid Oxide Fuel Cell Against Model Imperfections and Delay Phenomena

Abstract: Solid oxide fuel cell systems such as those presented in this paper are not only applicable for a pure supply with electric energy, they can typically also be used in decentralized power stations, i.e., as micro-cogeneration systems for houses, where both electric and thermal energy are required. For that application, obviously, the electric power need is not constant but rather changes over time. In such a way, it essentially depends on the user profiles of said houses which can refer to e.g., private househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Previous work of the author has shown that the electric power characteristic of SOFCs depends in a non-negligible way on the enthalphy flow of the supplied reaction media at the anode and cathode sides as well as on the internal temperature of the SOFC stack [13,25]. Corresponding system models then make use of a finite-volume discretization of the thermal system behavior according to Figure 1.…”
Section: Modeling Of the Electric Power Characteristic Of Solid Oxidementioning
confidence: 99%
See 4 more Smart Citations
“…Previous work of the author has shown that the electric power characteristic of SOFCs depends in a non-negligible way on the enthalphy flow of the supplied reaction media at the anode and cathode sides as well as on the internal temperature of the SOFC stack [13,25]. Corresponding system models then make use of a finite-volume discretization of the thermal system behavior according to Figure 1.…”
Section: Modeling Of the Electric Power Characteristic Of Solid Oxidementioning
confidence: 99%
“…This procedure relies on a principal component analysis that is based on a singular value decomposition approach [34]. In [33], it was shown that the most relevant input parameters, which were acquired in [13,33] with a sampling frequency of 10 Hz at a test rig available at the University of Rostock, Germany, are given by the quantities marked with the symbols in the first row of Table 2 Figure 1. Spatial semi-discretization of the fuel cell stack module (arrangement of finitely large volume elements in up to three space coordinates) [16].…”
Section: Static Neural Network Modelmentioning
confidence: 99%
See 3 more Smart Citations